(untitled) (South East Asia Journal of Public Health, 2015)
Low birth weight (LBW) is an important cause of perinatal, neonatal and post-natal morbidity and mortality. In developing countries, LBW of newborns is mainly due to the poor socio-economic and environmental conditions of the mother. The aim of the study was to identify and quantify the effects of age, religion, socio-economic status and occupation of mothers, in order to examine which factors were primarily responsible for LBW of babies. In this study, all singleton newborn having a weight of <2.5kg was included as a case and a weight of ?2.5kg was included as a control. The relation of birth-weight to few maternal factors such as age, socio-economic status, religion and occupation were studied. A total of 120 cases and 240 controls were selected. After selection of each case as defined, the next available two newborns that had fulfilled the criteria for controls given above were selected and included in the control group. This ensured a case:control ratio of 1:2. Our Study showed that the greatest number of mothers having LBW newborns were in the age group of 21 to 25 years (50% and 45.1% in both the cases and control groups respectively), belonged to socio-economic group V (42.5% and 40% in both groups respectively) and were Hindus (96.7% and 89.6% in both groups respectively). It was found that 70% of LBW babies were born to mothers who belonged to the labor class by occupation. This study concluded with the findings that maternal factors like age, socio-economic status, religion and occupation of the mothers were related to LBW of the newborns. Avoiding teenage pregnancies, improving the socio-economic status (SES) of people and providing better working DOI: http://dx.doi.org/10.3329/seajph.v4i1.21836 South East Asia Journal of Public Health Vol.4(1) 2014: 30-34